Kualitas Pelayanan Terhadap Kepuasan Nasabah Di Bmt Ugt Sidogiri Cabang Kotaanyar - Urip Santuso; Mufidatul Himmah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aimsto measure the level  of customer satisfacion with the services provided by BMT UGT CABANG KOTANYAAYAR. The methode  used in study is a survey with a questionnaire distributed  to customers. The variables tested  include product quality, service,and convenience. The results of the study indicate that most costumer are satisfed with the products offred, although three are severeal areas that ne to be improved such  as speed  of service and response to customer complains. The factors that most influence customer satisfaction are product quality and customer service this study is expected to provide recommendations for companies to improve service quality and increase customer loyality